The influence of maturational and morphological status pre- and post-menarche on the 100-m freestyle swimming performance of competitive teenagers - Beatriz Matias Avelino do Bonfim; Giordano Marcio Gatinho Bonuzzi; Vitoria Leite Domingues; Fernando Carvalheiro Reiser (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: This study investigated whether the difference anthropometric of swimmers pre- and post-menarche influence the motor performance of a 100-m freestyle swimming test. Methods: Twenty-five female swimmers participated in this study, nine swimmers have not had menarche (age 11.7 ± 0.63), and sixteen swimmers already have had it (age 15.17 ± 1.36). Body composition (skinfold thickness), anthropometrical parameters (height and weight), and biological age (Tanner self-assessment) were measured. A univariate and multivariate linear regression analysis was run to assess which personal or anthropometric variable predicts the motor performance (time trial) on a 100-m freestyle swimming test in pre- and post-menarche participants. As well, it was performed a Pearson's correlation test between the maturational status on Tanner self-assessment and the motor performance. Results: Post-menarche swimmers demonstrated better motor performance than pre-menarche swimmers. Anthropometric characteristics did not predict the motor performance of pre-menarche swimmers. Age, height, and weight predicted 47.8% of the motor performance of post-menarche swimmers. The Tanner classification demonstrated a strong negative correlation with swimming performance. Conclusion: Anthropometric characteristics only impacted the motor performance of post-menarche swimmers.